2021
DOI: 10.1038/s41598-021-92515-2
|View full text |Cite|
|
Sign up to set email alerts
|

Impairing flow-mediated endothelial remodeling reduces extravasation of tumor cells

Abstract: Tumor progression and metastatic dissemination are driven by cell-intrinsic and biomechanical cues that favor the growth of life-threatening secondary tumors. We recently identified pro-metastatic vascular regions with blood flow profiles that are permissive for the arrest of circulating tumor cells. We have further established that such flow profiles also control endothelial remodeling, which favors extravasation of arrested CTCs. Yet, how shear forces control endothelial remodeling is unknown. In the present… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 74 publications
0
25
0
Order By: Relevance
“…We have recently shown that endothelial cells also hijack a flow-stimulated pro-angiogenic transcriptional program to perform intravascular remodeling that favors the extravasation of arrested CTCs (Follain et al, 2018, 2021). It is tempting to speculate that tEVs could mediate such intravascular remodeling, whose dependence on flow forces is also established (Follain et al, 2021). Finally, one could expect that tEVs are continuously secreted after metastasis initiation, leading to the induction of neo-sprouts which sustain the growth of metastatic foci that have colonized distant organs (Kienast et al, 2010)(Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We have recently shown that endothelial cells also hijack a flow-stimulated pro-angiogenic transcriptional program to perform intravascular remodeling that favors the extravasation of arrested CTCs (Follain et al, 2018, 2021). It is tempting to speculate that tEVs could mediate such intravascular remodeling, whose dependence on flow forces is also established (Follain et al, 2021). Finally, one could expect that tEVs are continuously secreted after metastasis initiation, leading to the induction of neo-sprouts which sustain the growth of metastatic foci that have colonized distant organs (Kienast et al, 2010)(Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, Goetz et al recently uncovered the cellular and molecular mechanisms driving blood flow dependent arrest of circulating tumour cells, endothelial remodelling and extravasation thanks to this model. 51,52 The evolution of cell and nuclear volume as well as morphology throughout the cell cycle was also revealed thanks to the impressive efficiency of deep learning-based approach for 3D time-lapse multi-channel segmentation.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Microfluidic devices used to obtain the transcriptomics profile of endothelial cells cultured under capillary-like FSS revealed an upregulation of vascular endothelial growth factor receptor (VEGFR) signaling. Zebrafish treated with VEGFR inhibitors, including FDAapproved anti-angiogenic Sunitinib, presented impaired flow-mediated endothelial remodeling thus reducing CTCs extravasation (Follain et al, 2021). At the CTCs level, extravasation is enhanced by FSSdependent matrix metalloproteinases (MMP) upregulation (Qazi et al, 2013) and hyaluronic acid secretion that will bind to endothelial CD44 glycocalyx (Offeddu et al, 2021).…”
Section: Mechanoadaptation : Ctcs Force Their Way To Metastasismentioning
confidence: 99%
“…Such fluidic properties have profound impacts on the fate of CTCs. While the high flow velocity and FSS in arteries cause CTCs to face physical damage leading to cell fragmentation and death (Headley et al, 2016;Regmi et al, 2017), reduced flow profiles in veins favor CTCs intravascular arrest and extravasation (Follain et al, 2018(Follain et al, , 2021Osmani et al, 2019). The lower flow velocity and FSS in lymphatic compared to blood vessels (Dixon et al, 2006) might be less deleterious to CTCs.…”
Section: Introductionmentioning
confidence: 99%